Evaluation of single stage tympanomastoid surgery in unsafe chronic suppurative otitis media in Kashmiri population: a cross sectional study - Mir, Parvez Ahmed; Makhdoomi, Owais; Abbas, Syed Waseem (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic suppurative otitis media (CSOM) is typically a persistent disease insidious in ONSET, affecting the mucoperiosteal lining of middle ear cleft, often capable of causing severe destruction and irreversible sequelae and manifests clinically with hearing impairment and discharge. Successful management of unsafe CSOM has posed challenge before otolaryngologists for ages. Methods: The prospective study is based on 40 patients of unsafe CSOM who were managed and followed up in the post graduate department of otorhinolaryngology and head and neck surgery of Government medical college Srinagar with relevant data was recorded on the proforma. Results: All the patients who underwent single stage tympanomastoid surgery with or without ossicular chain reconstruction had no evidence of recurrent disease at follow up with 82.5% were below the age of 40, of which 40% were between 21 to 30 years. Males were more involved than females (1.2:1), also CT scan findings were co related with intra operative findings during our study. Conclusions: In conclusion a perfectly performed canal wall down mastoidectomy with tympanoplasty with us without ossiculoplasty in same sitting give good and acceptable post-operative results as far as the hearing improvement and dry and safe ear is concerned.